The formation of bulges, discs and two-component galaxies in the CANDELS Survey at z < 3 - Margalef-Bentabol, Berta; Conselice, Christopher J.; Mortlock, Alice; Hartley, Will; Duncan, Kenneth; Ferguson, Harry C.; Dekel, Avishai; Primack, Joel R. (Oxford University Press, 2016)
We examine a sample of 1495 galaxies in the CANDELS fields to determine the evolution of two-component galaxies, including bulges and discs, within massive galaxies at the epoch 1 < z < 3 when the Hubble sequence forms. We fit all of our galaxies’ light profiles with a single Sersic fit, as well as with a combination of exponential and Sersic profiles. The latter is done in order to describe a galaxy with an inner and an outer component, or bulge and disc component. We develop and use three classification methods (visual, F-test and the residual flux fraction) to separate our sample into one-component galaxies (disc/spheroids-like galaxies) and two-component galaxies (galaxies formed by an ‘inner part’ or bulge and an ‘outer part’ or disc). We then compare the results from using these three different ways to classify our galaxies. We find that the fraction of galaxies selected as two-component galaxies increases on average 50 per cent from the lowest mass bin to the most massive galaxies, and decreases with redshift by a factor of 4 from z = 1 to 3. We find that single Sersic ‘disc-like’ galaxies have the highest relative number densities at all redshifts, and that two-component galaxies have the greatest increase and become at par with Sersic discs by z = 1. We also find that the systems we classify as two-component galaxies have an increase in the sizes of their outer components, or ‘discs’, by about a factor of 3 from z = 3 to 1.5, while the inner components or ‘bulges’ stay roughly the same size. This suggests that these systems are growing from the inside out, whilst the bulges or protobulges are in place early in the history of these galaxies. This is also seen to a lesser degree in the growth of single ‘disc-like’ galaxies versus ‘spheroid-like’ galaxies over the same epoch.